Modified electrode and electrochemical sensor for detecting ascorbic acid as well as preparation method and application of modified electrode and electrochemical sensor
By using Cu-MOF-derived Cu2O/CuO composite material to modify the electrode, the problems of high limit of ascorbic acid detection and narrow linear range in the prior art are solved, and rapid and sensitive detection of ascorbic acid is achieved, with superior detection performance.
Patent Information
- Application Number
- CN202411713971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
AI Technical Summary
The methods used in the prior art for detecting ascorbic acid have problems such as high detection limit, narrow linear range, complex operation, poor anti-interference and long time consumption, which are difficult to meet the needs of rapid on-site detection.
Modified electrodes are prepared by using nano-scale Cu2O/CuO composite materials derived based on Cu-MOF. By combining with the substrate electrode, the electrochemical active sites and conductivity are improved, and the efficient detection of ascorbic acid is achieved.
It realizes rapid and sensitive detection of ascorbic acid, with a linear range of 1 to 2100 μmol/L, and a detection limit of 0.0741 μmol/L, and has excellent performance such as low detection limit, wide linear range, and good electrochemical activity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a modified electrode and an electrochemical sensor for detecting ascorbic acid, and a preparation method and application thereof, and belongs to the technical field of electrochemical sensors and electrochemical analysis. Background Art
[0002] Ascorbic acid plays a key physiological function in the human body, including enhancing immunity, promoting iron absorption, and participating in various metabolic reactions. Efficient and accurate detection of ascorbic acid content in body fluids is of great significance for evaluating nutrition and health status, disease diagnosis and drug efficacy monitoring. At present, although there are many methods for ascorbic acid detection, such as photometry, fluorescence, titration, etc., these methods generally have problems such as the need for complex analytical equipment, high analysis cost, cumbersome operation, poor anti-interference and long time consumption, which are difficult to meet the needs of rapid on-site detection. In contrast, electrochemical analysis has attracted much attention in the field of ascorbic acid detection due to its advantages such as high sensitivity, strong selectivity, high accuracy, simple instrumentation, convenient operation and rapid analysis. The performance of electrochemical sensors depends largely on the selection of electrode modification materials. Researchers are constantly exploring new combinations of modified electrode materials and preparation methods in order to obtain electrochemical sensors with excellent performance.
[0003] Metal-organic framework compounds (MOFs) are a new type of porous material with the advantages of large specific surface area, high porosity, low density, adjustable pore size and tailorability. They can be widely used in sensor manufacturing, energy storage, catalysis and trace detection. Among them, copper-based MOFs have become one of the hot candidates for electrochemical sensing materials due to their superior catalytic performance and variable valence. However, copper-based MOFs have problems such as poor conductivity, low signal conduction efficiency, and poor stability in water. In addition, it is difficult to closely combine with electrodes during the assembly process of electrochemical sensors, resulting in poor sensor stability, which limits their application in electrochemical sensors.
[0004] To solve these problems, using MOF materials as sacrificial templates and synthesizing MOF-derived nanomaterials for use as electrode modification materials has become a feasible solution. MOF-derived nano-oxide materials usually have good electrochemical properties, can improve the conductivity of materials, increase electrochemical active sites, and maintain the structural characteristics of the original MOF materials. They have been widely used in electroanalytical determination. The preparation of copper oxides using Cu-MOF-derived metal oxide templates has the characteristics of multi-level fine structure, highly ordered pore structure, larger specific surface area, and more contact active sites. It is expected to effectively regulate the composition and structure of metal oxides. However, the preparation of derived oxide materials using granular MOF materials as templates still faces problems such as small size, uneven distribution, brittle rigidity, and severe overlap, which seriously hinders its development in electrochemical sensors.
[0005] Therefore, it is of great research value and practical significance to develop a nanoscale Cu2O / CuO composite material derived from Cu-MOF and use it to prepare modified electrodes and electrochemical sensors to solve the problems existing in the prior art and achieve efficient, accurate and rapid detection of ascorbic acid.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a modified electrode for detecting ascorbic acid, the modified electrode exhibits good sensing ability, the linear range of ascorbic acid detection is 1-2100 μmol / L, the detection limit reaches 0.0741 μmol / L, and has superior performances such as low detection limit, wide linear range, and good electrochemical activity, thereby realizing rapid and sensitive detection of ascorbic acid. The present invention also provides a preparation method of the modified electrode, an electrochemical sensor comprising the modified electrode, and applications thereof.
[0008] The technical solution adopted by the present invention to solve the above problems is as follows:
[0009] A modified electrode for detecting ascorbic acid comprises a base electrode and a Cu2O / CuO composite material modified on the surface of the base electrode.
[0010] Preferably, the substrate electrode includes but is not limited to a glassy carbon electrode, a platinum electrode or a diamond electrode. More preferably, the substrate electrode is a glassy carbon electrode.
[0011] Furthermore, the preparation method of the Cu2O / CuO composite material includes: mixing and grinding the Cu-MOF material and ascorbic acid uniformly to obtain a mixture; and calcining the mixture to obtain the Cu2O / CuO composite material.
[0012] Preferably, the mass ratio of the Cu-MOF material to the ascorbic acid is 4:1 to 3. More preferably, the mass ratio of the Cu-MOF material to the ascorbic acid is 4:2.
[0013] Preferably, the calcination temperature is 300-500° C., and the calcination time is 2 h to 5 h.
[0014] More preferably, the calcination temperature is 300° C. and the calcination time is 3 h.
[0015] Furthermore, the preparation method of the Cu-MOF material comprises the following steps:
[0016] (1) Dispersing Cu(CH3COO)2·4H2O and an organic ligand in dimethylformamide respectively, stirring them fully until they are completely dissolved, to obtain a Cu(CH3COO)2 solution and an organic ligand solution;
[0017] (2) Mixing the organic ligand solution and the Cu(CH3COO)2 solution in a reaction kettle, placing the resulting mixed solution in a constant temperature drying oven for hydrothermal reaction to obtain a blue precipitate, washing and drying to obtain a Cu-MOF material.
[0018] Furthermore, the added amount of the Cu(CH3COO)2·4H2O is 0.05 to 1 mol; and the molar ratio of the Cu(CH3COO)2·4H2O to the organic ligand is 1:1.
[0019] Preferably, the organic ligand is at least one of terephthalic acid (BDC) and trimesic acid (BTC).
[0020] Preferably, the temperature of the hydrothermal reaction is 110° C. to 130° C., and the time is 10 h to 14 h. More preferably, the temperature of the hydrothermal reaction is 120° C., and the time is 12 h.
[0021] Preferably, the washing is washing the precipitate with ethanol for 5 to 6 times.
[0022] Preferably, the vacuum drying is carried out at a temperature of 80° C. to 110° C. and for a time of 8 h to 14 h.
[0023] A method for preparing a modified electrode for detecting ascorbic acid comprises the following steps: coating a mixed slurry comprising a Cu2O / CuO composite material and a binder on the surface of a base electrode, and obtaining the modified electrode after drying.
[0024] Preferably, the drying is natural drying at room temperature.
[0025] Preferably, the binder is 2% chitosan solution.
[0026] Preferably, the mass ratio of the Cu2O / CuO composite material to the binder is 100:1.
[0027] An electrochemical sensor comprises a counter electrode and a reference electrode, and also comprises the modified electrode as described above as a working electrode.
[0028] Preferably, the counter electrode includes but is not limited to a platinum wire or a carbon counter electrode, more preferably a platinum wire.
[0029] Preferably, the reference electrode includes but is not limited to an Ag / AgCl electrode, a saturated calomel reference electrode or a hydrogen electrode, more preferably an Ag / AgCl electrode.
[0030] More preferably, the electrochemical sensor comprises a platinum electrode as a counter electrode, an Ag / AgCl electrode as a reference electrode, and the Cu2O / CuO composite material modified glassy carbon electrode as a working electrode.
[0031] An application of the electrochemical sensor in detecting ascorbic acid.
[0032] The present invention has the following beneficial effects:
[0033] The modified electrode of the invention comprises a base electrode and a Cu2O / CuO composite material modified on the surface of the base electrode; the Cu2O / CuO composite material is prepared by using Cu-MOF as a template and ascorbic acid as an auxiliary reduction; the preparation method of the composite material increases electrochemical active sites, improves the electrical conductivity and charge transfer ability of the material, and enables the Cu2O / CuO composite material to have good electrochemical performance; the composite material is used in the detection of ascorbic acid, thereby solving the problems of insufficient electrical conductivity and low sensitivity of copper-based organic framework compound (Cu-MOF) materials in the electrochemical determination process.
[0034] The modified electrode of the present invention exhibits good sensing ability, the linear range of ascorbic acid detection is 1-2100 μmol / L, the detection limit reaches 0.0741 μmol / L, and has the advantages of low detection limit, wide linear range, good electrochemical activity, etc. The electrochemical sensor assembled based on the synthesized Cu2O / CuO composite material modified electrode of the present invention has excellent sensing performance, high selectivity and rapid detection ability for ascorbic acid, and realizes rapid and sensitive detection of ascorbic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 XRD patterns of the Cu-MOF material prepared in Preparation Example 1 and the five Cu2O / CuO composite materials prepared in Preparation Examples 2 to 6;
[0036] Figure 2 The SEM images of the Cu-MOF material prepared in Preparation Example 1 and the five Cu2O / CuO composite materials prepared in Preparation Examples 2 to 6;
[0037] Figure 3 The AC impedance diagrams of the modified electrodes of Examples 1-3 and Comparative Examples 1-3;
[0038] Figure 4 Cyclic voltammetry curves of the modified electrodes of Examples 1-3 and Comparative Examples 1-3 in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6];
[0039] Figure 5Cyclic voltammetry curves of each modified electrode of Examples 1-3 and Comparative Examples 1-3 in a 1 mmol / L ascorbic acid solution containing 0.1 mol / L PBS (pH 6);
[0040] Figure 6 Cyclic voltammetry curves of ascorbic acid on the Cu-MOF modified electrode of Comparative Example 3 at different scan rates;
[0041] Figure 7 Cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-0AA modified electrode of Comparative Example 1 at different scan rates;
[0042] Figure 8 Cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-50AA modified electrode of Example 2 at different scan rates;
[0043] Fig. 9 cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-100AA modified electrode of Example 1 at different scan rates;
[0044] Fig.10 The cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-150AA modified electrode of Example 3 at different scan rates;
[0045] Fig.11 Cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-200AA modified electrode of Comparative Example 2 at different scan rates;
[0046] Fig.12 DPV curves of each modified electrode of Examples 1-3 and Comparative Examples 1-3 in a 0.1M PBS solution (pH 6) containing 50 mmol / L ascorbic acid;
[0047] Fig.13 DPV curves of ascorbic acid on the Cu2O / CuO-100AA modified electrode of Example 1 at different pH values, a relationship diagram between redox peak potential and pH value, and a relationship diagram between oxidation peak current and pH value;
[0048] Fig.14 1 is a DPV curve diagram of ascorbic acid with different concentrations on the Cu2O / CuO-100AA modified electrode, and a linear relationship diagram between the ascorbic acid oxidation peak current and its concentration on the Cu2O / CuO-100AA modified electrode of Example 1. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Unless otherwise specified, the test materials, reagents, methods and equipment used in the following examples are conventional test materials, reagents, methods and equipment in the technical field; unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources. The quantitative tests in the following examples were all repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.
[0051] The reagents used in the following preparation examples and embodiments are shown in Table 1.
[0052] Table 1:
[0053]
[0054]
[0055] Preparation Example 1:
[0056] (1) 0.1 mol Cu(CH3COO)2·4H2O and 0.1 mol terephthalic acid are dispersed in 10 mL dimethylformamide respectively and stirred until completely dissolved to obtain a Cu(CH3COO)2 solution and a BDC solution; wherein the Cu(CH3COO)2 solution can be filled into a plastic tube after being fully dissolved, and then placed in an ultrasonic cleaner for 5 min to form a transparent solution.
[0057] (2) The BDC solution was transferred to a reactor container, and the Cu(CH3COO)2 solution was added dropwise at room temperature while stirring. After the addition was completed, the reactor cover was tightened, and the reactor was placed in a constant temperature drying oven for hydrothermal reaction (reacted at 120°C for 12 hours). The blue precipitate obtained by the reaction was collected by centrifugation, washed with ethanol for 5 to 6 times, and then placed in a vacuum oven (dried at 100°C for 12 hours) to obtain Cu-BDC material, i.e., Cu-MOF material.
[0058] Preparation Example 2:
[0059] Weigh 200 mg of the Cu-MOF material obtained in Preparation Example 1 and 100 mg of ascorbic acid, grind the two materials together for 10 min until fully mixed to obtain a mixture; transfer the mixture into a porcelain crucible, place it in a muffle furnace, heat it to 300 ° C at a heating rate of 5 ° C / min and calcine for 3 h, cool it to room temperature after completion, take out the sample, and obtain a Cu2O / CuO composite material; mark it as Cu2O / CuO-100AA.
[0060] Preparation Example 3:
[0061] The preparation method of the Cu2O / CuO composite material is the same as that of Preparation Example 2, except that the amount of ascorbic acid added in the preparation of the Cu2O / CuO composite material is 50 mg. The Cu2O / CuO composite material obtained in this Preparation Example 3 is marked as Cu2O / CuO-50AA.
[0062] Preparation Example 4:
[0063] The preparation method of the Cu2O / CuO composite material is the same as that of Preparation Example 2, except that the amount of ascorbic acid added in the preparation of the Cu2O / CuO composite material is 150 mg. The Cu2O / CuO composite material obtained in this Preparation Example 4 is marked as Cu2O / CuO-150AA.
[0064] Preparation Example 5:
[0065] The preparation method of the Cu2O / CuO composite material is the same as that of Preparation Example 2, except that the amount of ascorbic acid added in the preparation of the Cu2O / CuO composite material is 0 mg. The Cu2O / CuO composite material obtained in this Preparation Example 5 is marked as Cu2O / CuO-0AA.
[0066] Preparation Example 6:
[0067] The preparation method of the Cu2O / CuO composite material is the same as that of Preparation Example 2, except that the amount of ascorbic acid added in the preparation of the Cu2O / CuO composite material is 200 mg. The Cu2O / CuO composite material obtained in this Preparation Example 6 is marked as Cu2O / CuO-200AA.
[0068] The Cu-MOF material prepared in Preparation Example 1 and five Cu2O / CuO composite materials (Cu2O / CuO-0AA, Cu2O / CuO-50AA, Cu2O / CuO-100AA, Cu2O / CuO-150AA, Cu2O / CuO-200AA) prepared in Preparation Examples 2 to 6 were subjected to XRD and SEM detection.
[0069] The specific operations of XRD detection include: spreading the sample to be tested over the sample slot, compacting the sample with a glass sheet, cleaning the sample on the edge of the glass groove, and placing the sample slot into the instrument; fixing the sample on the sample stage; setting the sample scanning range to 5-80° and the scanning speed to 10° / min; starting the instrument and performing scanning observation; acquiring images and analyzing and studying the images.
[0070] The specific operations of SEM detection include: sticking conductive glue on the sample table, using a toothpick to dip a small amount of sample and smearing it on the conductive glue in order of the label. If any sample sticks to the outside of the conductive glue, it needs to be gently blown away with an ear bulb; placing the coated sample table in a gold plating instrument to gold-plate the sample, and then placing the sample table into the instrument for testing.
[0071] Figure 1 The XRD patterns of the Cu-MOF material prepared in Preparation Example 1 and the five Cu2O / CuO composite materials (Cu2O / CuO-0AA, Cu2O / CuO-50AA, Cu2O / CuO-100AA, Cu2O / CuO-150AA, Cu2O / CuO-200AA) prepared in Preparation Examples 2 to 6 are shown. Using Jade software to analyze this, it can be found that the XRD pattern of the prepared Cu-MOF material has obvious diffraction peaks in the range of 2θ angle of 5-30°, proving that Cu-MOF is successfully prepared. The XRD patterns of the Cu2O / CuO composite material obtained after calcination and decomposition of Cu-MOF are significantly different from those of the Cu-MOF material, and the characteristic diffraction peaks of the Cu-MOF material disappear, proving that a chemical reaction occurs in the process, and the crystal structure of Cu-MOF and the Cu-based oxide material derived therefrom are significantly different. Among them, all six samples have obvious diffraction peaks at 2θ of 33.1°, 35.0°, 38.8°, 48.0°, 53.5°, 58.0°, 62.7°, 66.0°, 67.1°, 72.5°, and 74.7°, which are consistent with the crystal structure characteristics of CuO (JCPDS No.44-0706); and diffraction peaks corresponding to Cu2O (JCPDS No.34-1354) appear at 2θ of 36.0° and 43.0°. This shows that the Cu2O / CuO composite material was successfully synthesized. In addition, from Figure 1 It can be found that with the increase of the amount of ascorbic acid added, the intensity of the XRD diffraction peak of Cu2O in the composite material increases. This shows that during the calcination of Cu-MOF, the ratio of CuO to Cu2O in the derivative product can be controlled by adjusting the amount of ascorbic acid added.
[0072] Figure 2The SEM images of the Cu-MOF material prepared in Preparation Example 1 and the five Cu2O / CuO composite materials (Cu2O / CuO-0AA, Cu2O / CuO-50AA, Cu2O / CuO-100AA, Cu2O / CuO-150AA, Cu2O / CuO-200AA) prepared in Preparation Examples 2 to 6 are shown in FIG. Figure 2 It can be seen that the Cu-MOF before calcination has a multi-level structure constructed by lamellar sheets, and the structure has a highly porous structure; after calcination, the morphology of the derived Cu2O / CuO sample is significantly different from that of the Cu-MOF sample, proving that drastic chemical changes and structural evolution occurred during the high-temperature calcination process; the derived Cu2O / CuO samples are densely packed with nano-scale fine thick flake particles, and a rich void structure is formed. This close contact and internal porous structure has a large specific surface area and rich electrochemical active sites, which can accelerate the electron transfer in the electrode catalytic reaction process and is expected to improve its electrochemical performance. In addition, there is no obvious difference in the scanning electron microscope images of Cu2O / CuO-0AA, Cu2O / CuO-50AA, Cu2O / CuO-100AA, Cu2O / CuO-150AA, and Cu2O / CuO-200AA, which shows that Cu2O and CuO have a good coexistence relationship.
[0073] Example 1: A modified electrode for detecting ascorbic acid
[0074] S1. Use 0.05μm Al2O3 polishing powder to add an appropriate amount of ultrapure water and mix well. Use the figure eight method to grind the surface of the glassy carbon electrode until the electrode surface is a bright mirror surface. Then use deionized water to rinse off the Al2O3 polishing powder on the surface of the glassy carbon electrode and dry it. Before modifying the glassy carbon electrode, use the glassy carbon electrode as the working electrode, the Ag / AgCl electrode as the reference electrode, and the platinum wire electrode as the auxiliary electrode to form a three-electrode system. Place it in a 5mmol / L potassium ferrocyanide solution (containing 0.1mol / LKCl) for cyclic voltammetry scanning to verify the reversibility of the electrode. The cyclic potential range is set to -0.1V~0.6V and the scan rate is set to 50mV / s. If [Fe(CN)6] 3- / 4- The peak potential difference of the redox reaction on the GCE was △Ep≤80mV, indicating that the electrode surface had met the requirements of cleaning and activation. The electrode was rinsed with deionized water and dried for use.
[0075] S2. Add 0.3 mg chitosan and 30 mg Cu2O / CuO-100AA prepared in Preparation Example 2 to 1.5 mL water, stir until fully mixed and dispersed to obtain a uniform slurry, and use a microinjector to evenly coat the mixed slurry on the surface of the glassy carbon electrode that meets the requirements, dry at room temperature, and form a layer of stable modification material film on the surface of the glassy carbon electrode to obtain a Cu2O / CuO-100AA modified electrode.
[0076] The Cu2O / CuO-100AA modified electrode prepared in Example 1 was used as the working electrode, a platinum electrode was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode to assemble a three-electrode test system, which was then connected to an electrochemical workstation to obtain an electrochemical sensor for quantitative detection of ascorbic acid.
[0077] Example 2: A modified electrode for detecting ascorbic acid
[0078] The preparation method of the modified electrode is the same as that of Example 1, except that Cu2O / CuO-100AA is replaced by Cu2O / CuO-50AA prepared in Preparation Example 3 to obtain a Cu2O / CuO-50AA modified electrode as a working electrode.
[0079] Example 3: A modified electrode for detecting ascorbic acid
[0080] The preparation method of the modified electrode is the same as that of Example 1, except that Cu2O / CuO-100AA is replaced by Cu2O / CuO-150AA prepared in Preparation Example 4 to obtain a Cu2O / CuO-150AA modified electrode as a working electrode.
[0081] Comparative Example 1: A modified electrode for detecting ascorbic acid
[0082] The preparation method of the modified electrode is the same as that of Example 1, except that Cu2O / CuO-100AA is replaced by Cu2O / CuO-0AA prepared in Preparation Example 5 to obtain a Cu2O / CuO-0AA modified electrode as a working electrode.
[0083] Comparative Example 2: A modified electrode for detecting ascorbic acid
[0084] The preparation method of the modified electrode is the same as that of Example 1, except that Cu2O / CuO-100AA is replaced by Cu2O / CuO-200AA prepared in Preparation Example 6 to obtain a Cu2O / CuO-200AA modified electrode as a working electrode.
[0085] Comparative Example 3: A modified electrode for detecting ascorbic acid
[0086] The preparation method of the modified electrode is the same as that of Example 1, except that Cu2O / CuO-100AA is replaced by the Cu-MOF material prepared in Preparation Example 1 to obtain a Cu-MOF modified electrode as a working electrode.
[0087] The modified electrodes prepared in the examples and comparative examples were subjected to the following electrochemical tests:
[0088] Test 1:
[0089] The impedance of each modified electrode of the embodiment and the comparative example was studied in a 5 mmol / L K3[Fe(CN)6] solution containing 0.1 mol / L KCl as a supporting electrolyte.
[0090] The results are as follows Figure 3 As shown, Figure 3 The AC impedance diagrams of the modified electrodes of Examples 1-3 and Comparative Examples 1-3;
[0091] from Figure 3 It can be seen that compared with the Cu-MOF modified electrode, the Cu2O / CuO composite modified electrode derived from Cu-MOF has a lower electrochemical impedance value and better conductivity, which can more effectively promote the electron transfer rate on the electrode surface. The Cu2O / CuO-100AA modified electrode has the lowest charge transfer resistance and the highest charge transfer rate, and the slope in the low frequency region is significantly greater than that of other modified electrodes. This shows that the diffusion mass transfer rate of the Cu2O / CuO-100AA modified electrode is faster, which is conducive to increasing the charge transfer power and promoting its interfacial electrochemical reaction, showing excellent conductivity and electrochemical performance.
[0092] Test 2:
[0093] Cyclic voltammetry was performed in a 5 mmol / L K3[Fe(CN)6] solution containing 0.1 mol / L KCl as a supporting electrolyte, with the scanning potential range set to -0.1 V to 0.6 V and the scanning rate set to 50 mV / s.
[0094] Test results such as Figure 4 As shown, Figure 4 Cyclic voltammetry curves of each modified electrode of Examples 1-3 and Comparative Examples 1-3 in a 5 mmol / L K3[Fe(CN)6] solution containing 0.1 mol / L KCl supporting electrolyte;
[0095] from Figure 4 It can be seen that the CV curves of the modified electrodes in the examples and comparative examples all have [Fe(CN)6] 3- / 4-The redox peak of the reversible reaction, but compared with the bare GCE, the Cu-MOF and Cu-MOF derived Cu2O / CuO composite modified electrodes show a smaller redox peak current response and a larger redox peak potential difference. This is due to the poor conductivity of MOF materials and copper-based oxides themselves. In addition, the Cu-MOF modified electrode has almost no redox peak current, which is due to the poor conductivity and electrochemical properties of the Cu-MOF material; while the Cu2O / CuO-100AA modified electrode has a pair of symmetrical and maximum redox currents. This shows that the Cu2O / CuO-100AA modified electrode has a strong electron transfer ability, which is beneficial to improve its electrochemical sensing performance.
[0096] Test 3:
[0097] Cyclic voltammetry was performed in 1 mmol / L ascorbic acid containing 0.1 mol / L PBS solution (pH=6), with the scanning potential range set to -0.4 V to 1.0 V and the scanning speed set to 50 mV / s.
[0098] Test results such as Figure 5 As shown, Figure 5 Cyclic voltammetry curves of each modified electrode of Examples 1-3 and Comparative Examples 1-3 in a 1 mmol / L ascorbic acid solution containing 0.1 mol / L PBS (pH 6);
[0099] from Figure 5 It can be seen that the redox current on the Cu-MOF modified electrode and the Cu2O / CuO-200AA modified electrode is weak, and the response to ascorbic acid is poor, while the redox current of the Cu2O / CuO-100AA modified electrode is strong, and the response to ascorbic acid is good, showing a pair of obvious redox peak electrochemical response signals and the highest redox peak current value, which indicates that Cu2O / CuO-100AA has excellent electrochemical catalytic performance for ascorbic acid and is more sensitive to the detection of ascorbic acid.
[0100] Test 4:
[0101] The other conditions remained unchanged, only the scanning speed was changed, and the cyclic voltammetry test was carried out to measure the CV curves of each modified electrode in the embodiment and the comparative example at different scanning speeds.
[0102] Test results such as Figure 6-10 As shown, Figure 6 Cyclic voltammetry curves of ascorbic acid on the Cu-MOF modified electrode of Comparative Example 3 at different scan rates; Figure 7 Cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-0AA modified electrode of Comparative Example 1 at different scan rates; Figure 8Cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-50AA modified electrode of Example 2 at different scan rates; Fig. 9 cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-100AA modified electrode of Example 1 at different scan rates; Fig.10 The cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-150AA modified electrode of Example 3 at different scan rates; Fig.11 The cyclic voltammetry curves of ascorbic acid on the Cu2O / CuO-200AA modified electrode of Comparative Example 2 at different scan rates.
[0103] from Figure 6-11 It can be seen that as the scan rate increases from 20mV / s to 140mV / s, the oxidation peak current and reduction peak current also increase gradually. At the same time, it is found that the redox peak current of ascorbic acid is linearly related to the first power of the scan rate. The linear regression equations (B1-B6) are respectively,
[0104] (1)Cu-MOF:
[0105] i pa (μA)=-3.7024+4.5427v 1 / 2 (R 2 =0.89830)
[0106] i pc (μA)=1.1410-4.8741v 1 / 2 (R 2 =0.93738)
[0107] (2) Cu2O / CuO-0AA:
[0108] ipa(μA)=-0.5469-0.03005v 1 / 2 (R 2 =0.97289)
[0109] ipc(μA)=0.26416-0.00288v 1 / 2 (R 2 =0.98835)
[0110] (3) Cu2O / CuO-50AA:
[0111] i pa (μA)=4.3829+1.4956v 1 / 2 (R 2 =0.99662)
[0112] i pc(μA)=-4.4931-1.8337v 1 / 2 (R 2 =0.99928)
[0113] (4)Cu2O / CuO-100AA:
[0114] i pa (μA)=6.8761+1.5822v 1 / 2 (R 2 =0.92254)
[0115] i pc (μA)=-9.2563-1.5062v 1 / 2 (R 2 =0.95814)
[0116] (5)Cu2O / CuO-150AA:
[0117] i pa (μA)=4.1162+1.8494v 1 / 2 (R 2 =0.83581)
[0118] i pc (μA)=-7.3520-1.4650v 1 / 2 (R 2 =0.77489)
[0119] (6)Cu2O / CuO-200AA:
[0120] i pa (μA)=4.8577+0.7980v 1 / 2 (R 2 =0.90309)
[0121] i pc (μA)=-6.6828-0.3354v 1 / 2 (R 2 =0.22381)
[0122] It can be seen that the redox peak current of ascorbic acid has a good linear relationship with the scan rate of one-half. When the scan rate decreases, the current response decreases and the sensitivity becomes worse. On the contrary, when the scan rate increases, the current response also increases, the sensitivity becomes higher, but the reversibility of the redox reaction becomes worse. The electrochemical redox process of ascorbic acid on Cu-MOF modified electrode, Cu2O / CuO-50AA modified electrode, Cu2O / CuO-100AA modified electrode, Cu2O / CuO-150AA modified electrode, and Cu2O / CuO-200AA modified electrode shows a typical diffusion-controlled process.
[0123] Test 5:
[0124] In a 0.1 M PBS solution (pH 5) containing 50 mmol / L ascorbic acid, a differential pulse voltammetry test was performed to study the sensing performance of each modified electrode in the examples and comparative examples to ascorbic acid.
[0125] The test results are shown in Figure 12. Fig.12 DPV curves of each modified electrode of Examples 1-3 and Comparative Examples 1-3 in a 0.1M PBS solution (pH 6) containing 50 mmol / L ascorbic acid;
[0126] from Fig.12 It can be seen that the Cu2O / CuO-100AA modified electrode produced the strongest electrochemical response signal and the highest oxidation peak current value during the electrocatalytic oxidation of ascorbic acid. This is because Cu2O / CuO-100AA has the best conductivity and more electrochemical active sites, which can induce rapid electron transfer, thereby greatly promoting the electrocatalytic oxidation process of ascorbic acid.
[0127] Test 6:
[0128] Test 5: Other conditions remain unchanged, only 0.1 mol / L PBS solution is prepared using dipotassium hydrogen phosphate, potassium dihydrogen phosphate or trisodium phosphate, and used to change the pH value of the ascorbic acid solution to be tested. The DPV curves of each modified electrode of the embodiment and the comparative example in 1 mmol / L ascorbic acid solution at different pH values are measured respectively.
[0129] Test results such as Fig.13 As shown, Fig.13 DPV curves of ascorbic acid on the Cu2O / CuO-100AA modified electrode of Example 1 at different pH values, a relationship diagram between redox peak potential and pH value, and a relationship diagram between oxidation peak current and pH value;
[0130] from Fig.13(A)-(C) It can be seen that with the gradual increase of pH value, that is, the gradual decrease of hydrogen ions in the electrolyte solution, the anodic oxidation peak potential of ascorbic acid gradually moves negatively, which indicates that protons participate in the electrochemical oxidation reaction of ascorbic acid. The Cu2O / CuO-100AA modified electrode has a good voltammetric response to ascorbic acid in the pH range of 5-7, and the maximum oxidation peak current of ascorbic acid is obtained at pH 6.
[0131] Test 7:
[0132] The best experimental conditions were selected: 0.1 mol / L PBS solution (pH 6), Cu2O / CuO-100AA modified electrode. The DPV curves of ascorbic acid at different concentrations on the Cu2O / CuO-100AA modified electrode in 0.1 mol / L PBS solution (pH 6) were measured respectively.
[0133] Test results such as Fig.14 As shown, Fig.14 1 is a DPV curve diagram of ascorbic acid with different concentrations on the Cu2O / CuO-100AA modified electrode, and a linear relationship diagram between the ascorbic acid oxidation peak current and its concentration on the Cu2O / CuO-100AA modified electrode of Example 1.
[0134] from Fig.14 (A) It can be seen that the DPV curves of ascorbic acid with different concentrations on the Cu2O / CuO-100AA modified electrode (a to o are 0, 150, 300, 450, 600, 750, 900, 1050, 1200, 1350, 1500, 1650, 1800, 1950, 2100 μmol / L); Fig.14 (B) It can be seen that as the concentration of ascorbic acid increases, the oxidation peak current also gradually increases. The oxidation peak current and ascorbic acid concentration are linearly related. In the range of 1 to 2100 μmol / L, the linear equation is i pa (μA)=0.8980+0.0096c AA (R 2 =0.9958), and the detection limit (S / N=3) was 0.0741 μmol / L.
[0135] Table 2 lists the analytical performance of some modified electrodes in the prior art for determining ascorbic acid.
[0136] Table 2:
[0137]
[0138]
[0139] As shown in Table 2, the electroanalytical performance of Cu2O / CuO-100AA for ascorbic acid, especially in terms of linear range and detection limit, is superior to that of other electrode modification materials.
[0140] By comparing the electroanalytical performance of different Cu2O / CuO composite modified electrodes in the examples and comparative examples, and studying the effects of morphology, structure and component differences on the analysis results, it can be found that the Cu2O / CuO-100AA modified electrode has good catalytic oxidation ability for ascorbic acid and exhibits good sensing ability. Under the optimized experimental conditions, the concentration of ascorbic acid and the response current show a good linear relationship, the linear range is 1-2100μmol / L, and the detection limit reaches 0.0741μmol / L, with low detection limit, wide linear range, good electrochemical activity and other superior performances. In general, the Cu2O / CuO composite material prepared based on the Cu-MOF sacrificial template derivatization has good sensing performance and application potential when used in modified electrodes and electrochemical sensors, and can achieve rapid and sensitive detection of ascorbic acid.
[0141] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0142] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0143] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A modified electrode for detecting ascorbic acid, characterized in that: The modified electrode comprises a base electrode and a Cu2O / CuO composite material modified on the surface of the base electrode.
2. The modified electrode for detecting ascorbic acid according to claim 1, characterized in that: The substrate electrode is a glassy carbon electrode, a platinum electrode or a diamond electrode.
3. The modified electrode for detecting ascorbic acid according to claim 1, characterized in that: The preparation method of the Cu2O / CuO composite material comprises: mixing and grinding Cu-MOF material and ascorbic acid uniformly to obtain a mixture; and calcining the mixture to obtain the Cu2O / CuO composite material.
4. The modified electrode for detecting ascorbic acid according to claim 3, characterized in that: The mass ratio of the Cu-MOF material to the ascorbic acid is 4:1-3.
5. The modified electrode for detecting ascorbic acid according to claim 3, characterized in that: The calcination temperature is 300-500° C., and the calcination time is 2 h-5 h.
6. The modified electrode for detecting ascorbic acid according to claim 3, characterized in that: The preparation method of the Cu-MOF material comprises the following steps: (1) Dispersing Cu(CH3COO)2·4H2O and an organic ligand in dimethylformamide respectively, stirring them fully until they are completely dissolved, to obtain a Cu(CH3COO)2 solution and an organic ligand solution; (2) Mixing the organic ligand solution and the Cu(CH3COO)2 solution in a reaction kettle, placing the resulting mixed solution in a constant temperature drying oven for hydrothermal reaction to obtain a blue precipitate, washing and drying to obtain a Cu-MOF material.
7. A method for preparing a modified electrode for detecting ascorbic acid according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: coating a mixed slurry comprising a Cu2O / CuO composite material and a binder on the surface of a base electrode, and obtaining the modified electrode after drying.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the Cu2O / CuO composite material to the binder is 100:
1.
9. An electrochemical sensor comprising a counter electrode and a reference electrode, characterized in that: The electrochemical sensor further comprises the modified electrode according to any one of claims 1 to 6 as a working electrode.
10. Use of the electrochemical sensor according to claim 9 in detecting ascorbic acid.